2006
DOI: 10.1002/mus.20525
|View full text |Cite
|
Sign up to set email alerts
|

Familial idiopathic hyper‐CK‐emia: An underrecognized condition

Abstract: Persistent elevation of serum creatine kinase (CK) in individuals with normal neurological and laboratory examinations has been called idiopathic hyperCKemia (IH). IH has been reported in rare families and was recently ascribed to caveolin-3 gene mutations. We retrospectively found that IH was familial in 13 of 28 subjects in whom serum CK was measured in relatives. These 13 families had a total of 41 subjects with IH, including six over 60 years of age. In eight families there was male-to-male transmission an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…In one study, 37 elevated CK was found in family members of 13 of 28 unrelated probands. In the 13 families, 41 individuals had elevated CK.…”
Section: Idiopathic Elevated Serum Ckmentioning
confidence: 94%
“…In one study, 37 elevated CK was found in family members of 13 of 28 unrelated probands. In the 13 families, 41 individuals had elevated CK.…”
Section: Idiopathic Elevated Serum Ckmentioning
confidence: 94%
“…Familial idiopathic hyperCKaemia is a benign genetically heterogeneous condition, with autosomal dominant features in a high proportion of cases and higher penetrance in males 5. Although many of these patients have been extensively investigated, the genetic defect underlying the hyperCKaemia has been identified in only a small number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Persistently elevated serum concentration of creatine kinase (CK) usually accompanies muscle weakness in patients with myopathies. However, it may also be found in individuals with a normal neurological examination, possibly due to subclinical or preclinical neuromuscular disorders, dystrophinopathy carrier state, hypothyroidism, hypoparathyroidism, alcoholism, or intake of statins and other drugs, and this condition is labeled asymptomatic hyperCKemia [78-80]. When the cause is not found, even after extensive investigations, the condition is defined as IH.…”
Section: Mhs and Association With Idiopathic Hyperckemia And Other Nementioning
confidence: 99%
“…When the cause is not found, even after extensive investigations, the condition is defined as IH. Capasso et al [80] studied a series of individuals with IH and found IH is familial in 46% of cases and familial IH is a benign genetically heterogeneous condition that is autosomal-dominant in at least 60% of cases, with higher penetrance in men.…”
Section: Mhs and Association With Idiopathic Hyperckemia And Other Nementioning
confidence: 99%